2021
DOI: 10.1111/ajo.13405
|View full text |Cite
|
Sign up to set email alerts
|

The health and educational costs of preterm birth to 18 years of age in Australia

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…A recent decision-analytic model estimated that for the first 18 years of life, a hypothetical birth cohort of 314,814 children - the number of total births in 2016 in Australia – a preterm birth rate of 8.5% will bear a cost of 1.413 billion Australian dollars, 39% of which is attributed to those born MLP. 7 A similar societal economic burden also exists within the US, where the current total incremental lifetime cost of an infant born MLP in 2016 is estimated to be 28,367 US dollars. 51 A 2016 MLP birth rate of 8.26% equated to 325,361 neonates being born MLP in the US.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent decision-analytic model estimated that for the first 18 years of life, a hypothetical birth cohort of 314,814 children - the number of total births in 2016 in Australia – a preterm birth rate of 8.5% will bear a cost of 1.413 billion Australian dollars, 39% of which is attributed to those born MLP. 7 A similar societal economic burden also exists within the US, where the current total incremental lifetime cost of an infant born MLP in 2016 is estimated to be 28,367 US dollars. 51 A 2016 MLP birth rate of 8.26% equated to 325,361 neonates being born MLP in the US.…”
Section: Discussionmentioning
confidence: 96%
“…4 , 5 , 6 As infants born MLP vastly outnumber very preterm (VP; 28 to <32 weeks’ gestation) and extremely preterm (EP; <28 weeks’ gestation) survivors, morbidity in those born MLP may result in substantial economic and healthcare burden. 7 …”
Section: Introductionmentioning
confidence: 99%
“…A further literature review has also revealed that during the last 50 years, preterm birth PTB has significantly impacted mortality rates during early and middle adulthood [8]. As well as contributing to lifelong disability, preterm birth imposes significant economic burdens on society [9]. Babies with low birth weights due to premature births have been at the forefront of the healthcare sector.…”
Section: Introductionmentioning
confidence: 99%
“…3 In Australia, an estimated A$1.4 billion is spent annually on healthcare and educational costs associated with preterm children until 18 years of age. 4 …”
Section: Introductionmentioning
confidence: 99%